Relationship between Sarcopenia in Abdomen CT Scan Results with C-Reactive Protein Level in Colorectal Cancer Patients at Dr. Soetomo General Academic Hospital Surabaya - Erlyta Dian Puspitarini; Prijambodo Prijambodo (Biomolecular and Health Science Journal, 2022)
Introduction: Colorectal cancer is the third most malignant and the fourth-largest cause of death in the world, one of which is caused by cachexia cancer. Sarcopenia is the main diagnostic criterion for cachexia. The inflammatory response, one of the markers of which is C-Reactive Protein (CRP), is also involved in the occurrence of sarcopenia associated with cachexia cancer. This study aimed to determine the occurrence of sarcopenia and its relationship with CRP preoperative colorectal cancer patients. Methods: This type of observational retrospective analytic study assessed sarcopenia based on the Psoas muscle index (IOP) on preoperative CT scan images and CRP levels measured by an integrated automatic tool Dimension RxL Max with Flex liquid reagent preoperative CRP range (RCRP). Results: Sarcopenia occurs in male colorectal cancer patients with a p-value of 0.001<0.05 (5%) with an IOP mean value of 26.75 m2, while in female patients the IOP mean value was 21.33 m2, it does not occur sarcopenia with p-value 0.583>0.05 (5%). There was an increase in CRP in 62.5% of colorectal cancer patients, but the relationship between IOP values and CRP values of colorectal cancer patients was still categorized as weak with p value of -0.387 in men and -0.046 in women with α=0.05. Conclusion: There was a nonsignificant relationship between sarcopenia and CRP levels in colorectal cancer patients. Further prospective studies are required to consider the indicators of sarcopenia besides the decrease in IOP and identification of confounding factors known to be associated with CRP, muscle strength, and muscle mass.